Pengaruh Minat Baca dan Penguasaan Kosakata terhadap Kemampuan Menulis Teks Deskriptif: Survei pada SMA Negeri di Kota Bekasi - Ana Zulfasari; Linang Marbun; Irwan Siagian (Neolectura, 2022)
The Effect of Reading Interest and Vocabulary Mastery on the Ability to Write Descriptive Text (Survey of Public High Schools in Bekasi City). This study aims to find out how reading interest and vocabulary mastery can affect a person's ability to write descriptive text. This study uses a survey method with multiple regression analysis, using a research paradigm between variables X1, X2, and Y. Then using the Slovin formula obtained a sample of 83 students, which then performed data analysis using the SPSS 20.0 application program. The results of the study prove that there is a significant influence on reading interest and vocabulary mastery on the ability to write descriptive texts.